NADPH oxidase-dependent free radical generation and protein adduct formation in neutrophils - Manoharan, Renuka Ramalingam; Zachová, Kateřina; Buzáš, Marek; Pospíšil, Pavel; Křupka, Michal; Prasad, Ankush (RSC advances, 2024)
Neutrophils mediate the early innate immune response through extracellular traps comprising intracellular protein and DNA. These traps play a pivotal role in both immunity against invading pathogens and the development of immunopathological reactions through the production of reactive oxygen species (ROS). Proteins serve as the main target for ROS, resulting in the formation of protein adducts. Herein, we report that the superoxide anion radical (O2˙-) plays a vital role in neutrophil function through sequential events involving 5-lipoxygenase (5-LOX) and NADPH oxidase (NOX). More specifically, differences in NOX homologs expression were observed post-stimulation with PMA and LPS. Differentiation conditions and O2˙- generation were confirmed using flow cytometry. Immunoblotting analysis confirmed the time-dependent expression of NOX underlying its requirement and 5-LOX-mediated lipid peroxidation events in neutrophil function. Protein-malondialdehyde (MDA) adducts formed were detected using immunoblotting, and quercetin was evaluated for its ability to scavenge free radicals through electron paramagnetic resonance (EPR) spin-trapping spectroscopy and results were confirmed with blotting analysis. Free radical-mediated protein oxidation events influence neutrophil function and protein adducts formed serve as markers of neutrophil activation upon infection and inflammation. The study warrants further corroboration and the study of specific proteins involved in neutrophil activation and their role in inflammation.